Issues Of Ensuring Food Security Under Climate Change Conditions (Texas Journal of Agriculture and Biological Sciences, 2025)
Sharp climate changes pose serious risks such as reduced water resources, an increase in natural disasters, and a decline in agricultural productivity, which altogether hinder the sustainable development of our region. These consequences primarily have a negative impact on vulnerable segments of the population